Consumer’s Behavioral Intention toward “Green” Restaurant: Empirical Evidence from Indonesia - Athaya Tsamara Zahra; Sri Rahayu Hijrah Hati (Fakultas Ekonomi, Universitas Negeri Jakarta, 2020)
This study specifically discusses the relationships between consumers’ environmental concern, attitude, subjective norms, perceived behavioral control, and their behavioral intention toward “green” restaurant. Such a study is important because behavioral intentions towards “green” practice in the restaurant industry is still an under-explored topic in the literature, despite the “green” trend. This study adopted Theory of Planned Behavior as the theoretical framework with additional environmental concern construct as antecedent. The findings from this research illustrate that customer’s environmental concern has a positive influence with behavioral intention toward “green” restaurant especially indirectly through attitude and perceived behavioral control. This study recommends that this topic of research needs to be explored more to understand the “green” restaurant customers and to develop marketing strategies to promote “green” restaurant in Indonesia.